KRITIK EVERETT REIMER TERHADAP LEMBAGA SEKOLAH DAN KONTRIBUSI PEMIKIRANNYA DALAM REDEFINISI MAKNA PENDIDIKAN - Gede Agus Siswadi (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2023)
Basically, humans need the education to be able to improve their quality of life and be able to develop all the competencies possessed by each individual. Thus, education becomes an important part of human life. Education actually has a very broad meaning and significance. However, in the view of society, education is always associated with schools. Even though school is just one part of education. This study aims to explore Everett Reimer's criticism of educational institutions, as well as Reimer's efforts to redefine the meaning of education. The method in this study is a qualitative method with a philosophical hermeneutic approach. The results of this study indicate that Reimer criticizes school institutions as having an attitude to realize that education is not narrowly defined only as a school. Reimer also succeeded in dismantling the establishment of schools in which there were forms of dehumanization. As an effort to redefine the meaning of education, Reimer offers an alternative school, namely a network of objects, a network of people, a network of peers, and also a network of educators.